2011
DOI: 10.1590/s1980-65742011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Esforço percebido e cinemática em percentuais da velocidade crítica na natação

Abstract: Resumo: O objetivo do presente estudo foi verificar os efeitos de diferentes percentuais da velocidade crítica (VC) na frequência cardíaca (FC), na frequência média de ciclos de braçadas (FB), na distância média que o corpo desloca a cada ciclo de braçada (DC) e no esforço percebido (EP) no nado crawl. Quinze nadadores, de ambos os sexos, realizaram cinco repetições de 200 m em diferentes percentuais da VC (90, 95, 100, 103 e 105%), em ordem aleatória. A FC, o EP e a FB apresentaram correlação significante pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition, [LA], although recognized as the standard for monitoring metabolic responses, is often difficult to use in daily training, basically due to economic and logistic issues 15 . On the other hand, HR and RPE are practical and inexpensive methods that can provide important information regarding the intensity used and the physiological status of swimmers 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, [LA], although recognized as the standard for monitoring metabolic responses, is often difficult to use in daily training, basically due to economic and logistic issues 15 . On the other hand, HR and RPE are practical and inexpensive methods that can provide important information regarding the intensity used and the physiological status of swimmers 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Tools applied to measure aerobic capacity used to be expensive and needs to be performed by an experiment team, which may impair its applicability. Thus, in young swimmers, Critical Speed (CS) has been recommended as powerful, easy and reliable tool to predict anaerobic threshold and evaluate aerobic capacity in a non-invasive way (Franken, Diefenthaeler, Carpes, & Castro, 2011;Wakayoshi et al, 1992;Wakayoshi et al, 1993). However, few studies has been observed the effects of a periodized physical training programs on aerobic capacity on young swimmers, particularly studying CS improvement.…”
Section: Introductionmentioning
confidence: 99%